Novel approach for secure cover file of hidden data in the unused area within EXE file using computation between cryptography and steganography - Naji, Ahmed Wathik; Zaidan, B.B.; Hameed, Shihab A.; O-Khalifa, Othman (IJCSNS, 2009)
The strength of the information hiding science is due to the non-existence of standard algorithms to be used in hiding secret messages. Also there is randomness in hiding methods such as combining several media (covers) with different methods to pass a secret message. In addition, there are no formal methods to be followed to discover the hidden data. For this reason, the task of this paper becomes difficult. In this paper a new method is implementing to hide a file of unused area 2 within .EXE file and to detect the hidden file. The aim of this paper is implementation of system computation between Cryptography and Steganography which embeds information in unused area 2 within EXE files to find a secure solution to cover file without change the size of cover file. The system includes two main functions; first is the hiding of the information in unused area 2 of PE-file (.EXE file), through the execution of four process (specify the cover file, specify the information file, encryption of the information, and hiding the information) and the second function is the extraction of the hiding information through three process (specify the steno file, extract the information, and decryption of the information) and The proposed system is implemented by using java.